Genesis of the Popular Front in Spain (1934-1936) - Jorge De Hoyos Puente (Ибероамериканские тетради)
This article studies the discussions and interpretations existing in Spain today about the political nature of the electoral coalition known as the Popular Front. In addition to presenting the debates, the article explains the process of formation of the Popular Front